THE REASONS OF CEO TURNOVERS: A NEW EVIDENCE FROM UK LISTED FIRMS - Pananda Pasaribu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2016)
The classification of CEO turnovers should be done properly in order to get robust empirical evidence on the studies of CEO turnover. Previous studies tend to rely only the official announcement of firms (CEOs) as the base of the classification. The study shows this approach may incorrectly classify CEO turnovers, particularly with pursue other interest reason, family reason, personal reason and health reason. Therefore, it is necessary to examine any news or recent report that are related to CEO turnover.Â Keywords: Corporate Governance, CEO Turnover